Pemberdayaan Santri Pesantren Raden Rahmat Sunan Ampel Jember di Masa Pandemi Covid-19 melalui Produksi Rengginang Singkong - Nurud Diniyah; Retno Purwandari; Dani Setiawan; Ni Ketut Leseni; Nugraha Yuwana (Universitas Muhammadiyah Surakarta, 2022)
The Raden Rahmat Sunan Ampel Islamic Boarding School located 2.1 km from Jember University on Jalan Koptu Berlian with students totaling approximately 70 from the University of Jember, Jember State Polytechnic and Muhammadiyah University of Jember. One of the boarding schools' efforts is to produce cassava’s rengginang. The problems faced by partners include nutritional content of cassava rengginang that has not been analyzed, the innovative potential and entrepreneurial spirit of the students, and the lack of understanding of stress management in the face of covid-19 pandemic. The solutions that can be offered from the proposing team to partner problems are providing training on rengginang production, training and mentoring of production, analysis of the nutritional content of cassava rengginang, mentoring students in participating in competitions, as well as additional activities, health and protocols related to covid prevention during the production process and stress management during the pandemic. The contribution from the partner audience is empowerment of students as participants and to train the entrepreneurial spirit, to be independent, creative and innovative and to be able to read business opportunities. The method of implementing this service activity is in the form of lectures, discussions, mentoring, practice and counseling. The results were carried out in several stages, namely the observation and coordination, counseling of material, the practice of making cassava rengginang, mentoring innovative soft skills and entrepreneurship, as well as conducting proximate tests on products, providing assistance with cassava raw materials and personal protective equipment such as masks, hand sanitizers and hand shoaps.